Changes in speed, agility and body composition of top-ranked female handball players during the playing season - Bojic, I.; Stojiljkovic, N.; Valdevit, Z.; Velickovic, M.; Nikolic, D. (Facta Universitatis: Series Physical Education and Sport, 2019)
Handball is a dynamic Olympic sport dominated by acyclic movements (sudden changes in direction, jumps, landings, contacts between the players, etc.) with speed and agility playing an important role in their successful realization. Our aim was to establish which changes occurred in the body composition, speed and agility of top-ranked female handball players during the playing season. The parameters for estimating body composition were: body mass, body mass index (BMI), the percentage of muscle and fat. The ability to achieve speed (in 5, 10 and 30m sprints) and agility (new envelope test without a ball, straight slalom run without a ball and Straight slalom run with a ball, zig-zag with and zig-zag without a ball) was estimated with the portable timing system. The differences between the initial and the final measurements were established with the Student`s t-test. The results obtained show that there were statistically significant changes and weaker results in almost all the tested variables. The only improvements were detected in the maximum speed in 30m sprint and the agility without a ball (new envelope test and slalom run without a ball). It is recommended that the training plan should be carefully devised (the activities of the high intensity load should be applied throughout the season) as well as the plan for proper sports nutrition (body mass should be reduced with simultaneous increase in the muscular mass component).